2017
DOI: 10.1039/c7sc03372a
|View full text |Cite
|
Sign up to set email alerts
|

Chromium complexes for luminescence, solar cells, photoredox catalysis, upconversion, and phototriggered NO release

Abstract: Cr(iii) and Cr(0) complexes are earth-abundant alternatives to photosensitizers that are commonly made from precious metals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
97
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 71 publications
(100 reference statements)
0
97
0
Order By: Relevance
“…[9] The" molecular ruby" 1 3+ Scheme 1. [8,10,11,[14][15][16] In many of the above-mentioned complexes (Scheme 1), detrimental ligand-field excited states, [17,18] which lead to nonradiative deactivation, are either absent (d 0 and d 10 electron configuration) or have been successfully shifted to highenough energy,sothat these states do not provide an efficient deactivation pathway.A st hese typically dissociative ligandfield states are not populated for as ufficiently long time, photosubstitution is virtually impossible.This photostability is especially pronounced for 1 3+ with ah igh-energy 4 T 2 ligandfield state preventing substitution reactions (k chem ;F igure 1, center) as back-intersystem crossing (BISC) from the doublet states to the 4 T 2 state is thermodynamically impeded (k BISC ; Figure 1, center). [4][5][6][7][8] [*] C. Wang displays asharp,unprecedentedly intense spin-flip emission in the NIR with aphotoluminescence quantum yield of F = 0.11 and al uminescence lifetime of t = 898 msi nH 2 Oa tr oom temperature.…”
mentioning
confidence: 99%
“…[9] The" molecular ruby" 1 3+ Scheme 1. [8,10,11,[14][15][16] In many of the above-mentioned complexes (Scheme 1), detrimental ligand-field excited states, [17,18] which lead to nonradiative deactivation, are either absent (d 0 and d 10 electron configuration) or have been successfully shifted to highenough energy,sothat these states do not provide an efficient deactivation pathway.A st hese typically dissociative ligandfield states are not populated for as ufficiently long time, photosubstitution is virtually impossible.This photostability is especially pronounced for 1 3+ with ah igh-energy 4 T 2 ligandfield state preventing substitution reactions (k chem ;F igure 1, center) as back-intersystem crossing (BISC) from the doublet states to the 4 T 2 state is thermodynamically impeded (k BISC ; Figure 1, center). [4][5][6][7][8] [*] C. Wang displays asharp,unprecedentedly intense spin-flip emission in the NIR with aphotoluminescence quantum yield of F = 0.11 and al uminescence lifetime of t = 898 msi nH 2 Oa tr oom temperature.…”
mentioning
confidence: 99%
“…[4] Some fruitful approaches to destabilize the energy of the 3 MC states consist of a) introduction of strong donor ligands and b) the use of tridentate ligands that form 6-membered chelate rings to reduce the steric strain and achieve am ore octahedral geometry compared to those bearing five-membered chelate rings. Recently,W enger and Gray et al observed 3 MLCT emission of earth abundant low-valent Cr 0 , [13] Mo 0 , [14] and W 0 [15] complexes with arylisocyanide ligands. Recently,W enger and Gray et al observed 3 MLCT emission of earth abundant low-valent Cr 0 , [13] Mo 0 , [14] and W 0 [15] complexes with arylisocyanide ligands.…”
mentioning
confidence: 99%
“…Following these approaches,Ru II , [5,6] Cr III , [7] and Fe((III), low spin) [8] complexes with strongly s-donating tridentate ligands have been shown to have dramatically longer emission lifetimes.A nother popular strategy to induce emission in 1 st row transition metals is to use d [10] metal-ions to avoid nonemissive d-d transition, for example,Cu I , [9] Ni 0 , [10] and Zn II ; [11] however, their MLCT excited states often undergo strong geometrical distortion [12] and non-radiative relaxation to the ground state can be rapid. Recently,W enger and Gray et al observed 3 MLCT emission of earth abundant low-valent Cr 0 , [13] Mo 0 , [14] and W 0 [15] complexes with arylisocyanide ligands. [16] Some of these complexes have been explored as photoredox catalysts in Diels-Alder reactions, [7] alkylations, and oxidative cyclizations, [17] trifluoromethylation of alkenes, [9] and polymerization.…”
mentioning
confidence: 99%